PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KARAKTERISTIK DEWAN KOMISARIS TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO (Studi empiris pada laporan tahunan perusahaan-perusahaan non-keuangan yang terdaftar di BEI tahun 2012) - Kusumaningrum, Amalia Ratna; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
Along with the development of the company and the business environment investors are more careful to put the investment in the company to prioritize disclosures in the financial statements. One of the important information that is of particular concern for investors is the non-financial segment of the annual report (Amran et al., 2009). This research purpose to get emprical proof about the factors which influential risk disclosure in the risk management report that is, institutional investors, independent commissioner, commissioner’s education background and commissioner’s experience on the risk management disclosure.This research use purposive sampling in carry out sample selection. Total population in this study were 387 non-financial firms and the samples used in this research were 77 non-financial companies in 2012. Agency theory and resource dependence theory  is used to explain connection inter variable. Act of risk disclosure in this research use content analysis based on the identification of setences act of risk disclosure in the annual report. Statistic method is use for examine hypothesis is bifilar regression. The test results shows that the risk management disclosure level in Indonesia is relatively high. This study provides evidence that institutional investors play a more effective role in monitoring the company's risk management disclosure compared to the board of directors. The results also show that commissioner’s education background and commissioner’s experience are  attributes associated with risk managemen disclosure.